Maternal and Fetal Attachment before Birth: Trends in Pregnant Women of Urban Karachi - Shelina Bhamani; Anita Attaullah; Hajra Malik; Faiqa Binte Aamir; Areeba Syed; Amir Raza; Lumaan Sheikh (International Journal on Women Empowerment, 2022)
Background: Maternal-fetal attachment is a multidimensional phenomenon and product of diverse physiological, psychological, and socio-emotional factors. Prenatal period plays a crucial role in forming this bond and further predicts post-natal attachment. Methods: The present research was conducted using cross-sectional survey design. 66 participants filled the survey regarding practices, perceptions and attitudes of maternal-fetal attachment, after attending an online session on “Talking to the Baby in the Womb”. Results: Analysis revealed that participants eat healthy during prenatal period and talk to their baby in tummy. Wondering when the baby starts thinking, feeling and hearing within also aids in forming maternal-fetal relationship. Statistically significant difference (p=0.013) was found between HCP and PW in terms of attitude towards feeding the baby and perception of mother giving up for the baby (p=0.04). Conclusion: Following research allows us to study the differences in the practices between healthcare providers and pregnant women so that interventions can be designed accordingly.